Is cultural group selection enough? - Read, Dwight (Behavioral and Brain Sciences, 2016)
Abstract Richerson et al. propose cultural group selection (CGS) as the basis for understanding the evolution of cultural systems. Their proposal does not take into account the nature of cultural idea systems as being constituted at an organizational, rather than an individual level. The sealing partners of the Netsilik Inuit exemplify the problem with their account.